Penerapan Metode User Centered Pada User Interface Sicyca Mobile - Muhammad Rizqi Farhandy Akbar; Erwin Sutomo; Endra Rahmawati (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2022)
One of the information technology services available at Dinamika University is the Academic Information System or better known as SICYCA (Cyber Campus Information System). Sicyca is an academic information system application that provides student academic information. Sicyca has 2 (two) versions of the application, namely the web version and the Mobile version. Based on the results of a questionnaire involving Dinamika University students, problems were found in the Sicyca Mobile application. Based on the evaluation of the initial design using the User Experience Questionnaire (UEQ), the initial design of the Sicyca Mobile application has an average of 0.05 and is included in the "bad" criteria so that design improvements are needed. To fix display problems in the Sicyca Mobile application, the solution given is to analyze and develop the user interface design on the Sicyca Mobile application using the User-Centered Design (UCD) method. Modification of the User Experience Questionnaire (UEQ) method used to develop the design development. The result of this research is the design of 18 user interfaces based on the UCD method, the UI Style Guide as a design guideline. The results of the design evaluation using the UEQ modification concluded that the overall average (average) had increased from 0.05 to 1.3, and indicated that the UEQ aspect had increased and entered the "above average" criteria, which means that the design user interface created can solve the problems that exist in the Sicyca Mobile application.